2012
DOI: 10.1128/aac.05943-11
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of the S769N Mutation in Plasmodium falciparum SERCA (PfATP6) with Resistance to Artemisinins

Abstract: The recent emergence of artemisinin (ART) resistance in Plasmodium falciparum in western Cambodia, manifested as delayed parasite clearance, is a big threat to the long-term efficacy of this family of antimalarial drugs. Among the multiple candidate genes associated with ART resistance in P. falciparum, the sarcoplasmic/endoplasmic reticulum Ca 2؉ -ATPase PfATP6 has been postulated as a specific target of ARTs. The PfATP6 gene harbors multiple single-nucleotide polymorphisms in field parasite populations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
2
37
0
1
Order By: Relevance
“…Several reports have implicated ATP6 as a target of the front-line artemisinin family of antimalarials (70), but recent efforts have demonstrated that this is not the case (71,72). However, these calcium stores can be released from the endoplasmic reticulum to the cytosol by increased levels of inositol trisphosphate, likely via a yet-to-be-identified inositol trisphosphate receptor or ryanodine receptor associated with the endoplasmic reticulum (51).…”
Section: A Selected Group Of Putative Surface-exposed Sporozoite Protmentioning
confidence: 99%
“…Several reports have implicated ATP6 as a target of the front-line artemisinin family of antimalarials (70), but recent efforts have demonstrated that this is not the case (71,72). However, these calcium stores can be released from the endoplasmic reticulum to the cytosol by increased levels of inositol trisphosphate, likely via a yet-to-be-identified inositol trisphosphate receptor or ryanodine receptor associated with the endoplasmic reticulum (51).…”
Section: A Selected Group Of Putative Surface-exposed Sporozoite Protmentioning
confidence: 99%
“…We originally targeted the pfatpase6 gene, because it carried an SNP (S769N) that was associated with lowered sensitivity to artemether in an earlier investigation in French Guiana 20 ; however, we did not detect the S769N mutation in our preliminary sample (data not shown). With more recent studies unable to confirm the association of the S769N mutation with artemisinin resistance in other populations 21,22 and the recent identification of the K13-propeller as a strong candidate for artemisinin resistance, we decided to refocus our investigation on K13-propeller polymorphisms. To contribute to the growing knowledge about the global genetic diversity of the K13-propeller and establish a baseline for future surveillance of potential artemisinin resistance in Haiti, we sequenced an 810-base pair region of the K13-propeller from P. falciparum samples collected in Haiti between 2010 and 2013.…”
mentioning
confidence: 99%
“…Also, in Southern-Iran, L263 and A623 were reported to be wild type (Zakeri et al 2012). The presence of S769N also made occasional impacts from few studies (Jambou et al 2005;Pillai et al 2012;Zakeri et al 2012) like that of the French Guiana (Legrand et al 2008) while there are reports which observed its absence in the P. falciparum isolates that were analyzed (Mugittu et al 2006;Sisowath et al 2007;Zhang et al 2008;Ferreira et al 2008;Menegon et al 2009;Wangai et al 2011;Kwansa-Bentum et al 2011;Tanabe et al 2011;Brasil et al 2012;Saha et al 2013) or even denied the association of this SNP with artemisinin resistance (Phompradit et al 2011;Cui et al 2012). Another study from Yaounde, Cameroon, where all these four mutations were tested, high prevalence of E431K was warranted and alarmed (Tahar et al 2009).…”
Section: Discussionmentioning
confidence: 89%